Litmus : short stories from modern science / edited by Ra Page. - Page, Ra, 1972- (Manchester : Comma, 2011)
"Like the creation myths they supersede, the revelations of science are seared into our collective imagination through storytelling. From Archimedes' bath to Newton's apple, vivid accounts of scientific discovery help us understand the principles behind each theory, and add to the larger narrative of how the universe works, and how we came to be here. This anthology draws out and distills science's love of narrative from a wide range of scientific disciplines, weaving theory into very human stories, and delving into the humanity of theorists and experimenters as they stood on the brink of momentous discoveries: from Joseph Swan's original light-bulb moment to the uncovering of 'mirror neurons' lighting up empathy zones in the human brain; from Einstein's revelation on a Bern tram, to Pavlov's identification of personality types thanks to a freak flood in his St. Petersburg lab. Each story has been written in close consultation with scientists and historians and is accompanied by a specially written afterword, expanding on the science for the general reader."--Publisher description.
The pitch / Frank Cottrell Boyce ; afterword by Kathryn Harris -- Patience / Emma Jane Unsworth ; afterword by Zoe Schnepp -- Swan, 1914 / Sean O'Brien ; afterword by John Clayson -- The special theory / Michael Jecks ; afterword by Jim Al-Khalili -- Everything is moving, everything is joined / Stella Duffy ; afterword by Robert Appleby -- The woman who measured the heavens with a span / Sara Maitland ; afterword by Tim O'Brien -- What kind of dog / Annie Clarkson ; afterword by John Wearden -- Crystal night / Zoe Lambert ; afterword by James Sumner -- Morphogenesis / Jane Rogers ; afterword by Martyn Amos -- The heart of Denis Noble / Alison MacLeod ; afterword by Denis Noble -- We are all made of protein / Tania Hershman ; afterword by Nick R. Love -- In search of silence / Adam Marek ; afterword by Tim O'Brien -- Living with insects / Maggie Gee ; afterword by Matthew Cobb -- Bride Hill / Kate Clanchy ; afterword by Sarah Fox -- What if? / Christine Poulson ; afterword by Angharad Watson -- Monkey see, monkey do / Trevor Hoyle ; afterword by Giacomo Rizzolatti -- That is the day / Sarah Hall ; afterword by James Higgerson.
"Eureka Moments covered in the collection: Jeremiah Horrocks & the transit of Venus, 1639 ; Dmitri Mendeleev's periodic table, 1869 ; Joseph Swan's electric light-bulb, 1880 ; Einstein's special relativity revelation, 1905 ; Hermann Minkowski's spacetime, 1908 ; Henrietta Leavitt's period-luminosity relation, 1912 ; Pavlov's flood and the transmarginal inhibition, 1924 ; Lise Meitner & the discovery of fission, 1939 ; Alan Turing's morphogenesis, 1952 ; Denis Noble and mathematically modeling the heart, 1960 ; Green florescent protein, 1961 ; Hamilton's Law and inclusive fitness, 1964 ; The cosmic microwave background, 1965 ; HM, Brenda Milner & the hippocampus, 1971 ; Kary Mullis' polymerase chain reaction, 1983 ; Giacomo Rizzolatti's mirror neurons, 2003 ; The discovery and treatment of AIDS, 1981-present."--Publisher website.
Keywords: Discoveries in science -- Fiction; Short stories, English -- 21st century